Debatten om svenskans ställning i Europa - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2007)
Swedish EU-access in January 1995 triggered off a widespread linguistic debatę on the futurę of the Swedish language in the united Europę. Despite its status as one of the Union's ofRcial languages, Swedish is often referred to as a minority language threatened by English. The debatę mentions current language policies of the E U , linguistic and non-linguistic aspects of the influence of one language on another and presents a number of solutions strengthening the status of the weaker language. Both the arguments and proposals can be interesting as new accessions are awaited and the debatę on Europeanisation is present even in the Polish linguistics.